Crustal and upper mantle structure beneath the Corinth rift (Greece) from a teleseismic tomography study - Tiberi, Christel; Lyon-Caen, Hélène; Hatzfeld, Denis; Achauer, Ulrich; Karagianni, E.; Kiratzi, A.; Louvari, E.; Panagiotopoulos, D.; Kassaras, I.; Kaviris, G.; Makropoulos, K.; Papadimitriou, P. (Journal of Geophysical Research: Solid Earth, 2000)
We report here the results of a tomographic lithospheric study in the area of the Corinth and Evvia rifts (Greece), designed to constrain the mechanism of continental extension. Sixty seismological stations were deployed in the area for a period of 6 months, and 177 teleseismic events were recorded by more than five stations and gave more than 2000 travel time residuals (P and PKP phases), which were inverted to image the velocity structure down to 200 km depth. We use both a linear and a nonlinear method to invert the data set. The main result is a long-wavelength positive velocity anomaly located in the upper mantle, which is interpreted as the subducted African lithosphere. The subducted lithosphere is well defined from ∼7O km depth down to 200 km. From synthetic tests as well as from the amplitude of the anomaly (more than +7%) we conclude that the subduction continues below 200 km. In addition, a second positive velocity anomaly of about +4% from the surface down to 40 km depth, located north of the Gulf of Corinth, has been found. This is interpreted as the result of a crustal thinning of several kilometers (∼5 km), shifted to the north from the Gulf of Corinth and trending obliquily NW-SE. We suggest that this crustal thinning is mainly related to the Miocene widespread extension in the Aegean and that the Quaternary Corinth rift initiated where the crust was already thinned. The different styles of deformation of the eastern and western part of the rift are consistent with this interpretation. No clear velocity anomaly can be related to the Evvia rift.